The Representation of Collocational Patterns and Their Differentiating Power in the Speaking Performance of Iranian IELTS Test-Takers - Estaji, Masoomeh; Montazeri, Mohammad Reza (Frontiers in Education, 2022)
Corpus studies have highlighted the role of multiword units in naturally occurring language. Speech theories, too, have underlined the linkage between such formulaic sequences- collocations in particular- and speech production. Few studies, however, have focused their attention on examining collocations in speaking assessment, especially in high-stakes tests. This study investigated the most frequently used collocational patterns and their discriminating power across three groups of participants with band scores 6, 7, and 8 respectively. To collect data, a corpus entailing 60 IELTS speaking samples, 20 samples from each band score, and approximately 110,000 words was gleaned. The results revealed that L1 (adjective + noun) and L7 (verb + noun) were the most frequently used types of lexical collocations, and G8 (verb + preposition) was the most frequently used grammatical collocation. The study also found that L1(adjective + verb), L5 (noun of noun), L8 (phrasal verb and adverb), L9 (noun and phrasal verb), and L10 (phrasal verb and noun) were the five types of lexical collocations with the most discriminating power across the band scores. Given the grammatical collocations, G4 (preposition + noun) and G5 (adjective + preposition) had the power to differentiate across the three band scores.